1992
DOI: 10.1007/bf00160209
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide variation and molecular structure of the heterochromatic repetitive AluI DNA in the brine shrimp Artemia franciscana

Abstract: It has been suggested that DNA bending could play a role in the regulation of gene expression, chromosome segregation, specific recombination and/or DNA packaging. We have previously demonstrated that an AluI DNA family of repeats is the major component of constitutive heterochromatin in the brine shrimp A. franciscana. By the analysis of cloned oligomeric (monomer to hexamer) heterochromatic fragments we verified that the repetitive AluI DNA shows a stable curvature that determines a solenoidal geometry to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…This variability, together with the data obtained regarding the distribution of the AluI-113bp satellite DNA (Landsberger et al 1992), could indicate that this species is actually expanding, from an evolutionary point of view, more actively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This variability, together with the data obtained regarding the distribution of the AluI-113bp satellite DNA (Landsberger et al 1992), could indicate that this species is actually expanding, from an evolutionary point of view, more actively.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years attempts were made (Badaracco et al 1987;Landsberger et al 1992) to correlate some populations living in different regions of the world by means of a molecular approach utilizing a repetitive AluI heterochromatic sequence as probe (Barigozzi et al 1984;Cruces et al 1986). The results showed a great variation (more than 100-fold) in the copy number of the AluI fragment of the American strains, revealing the existence of a gradient of heterochromatin amount increasing from the south to the north of the continent.…”
Section: Introductionmentioning
confidence: 99%
“…BARIGOZZI et al (1984), BADARACCO et al (1987;1991) and LANDSBERGER et al (1992) used the AluI-type of repetitive DNA. PEREZ et al (1994) first analyzed the mtDNA and concluded that A. salina, A. franciscana and two parthenogenetic strains should be considered as belonging to different species.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the DNA of contemporary cysts is the continuing object of study (Kim et al, 1992;Landsberger et al, 1992;Escalente et al, 1994;Franco et al, 1994;Jellie et al, 1996;Ortega et al, 1996) and the complete sequence of their mitochondrial DNA has recently been published (Valverde et al, 1994), providing a basis for future comparison with sequences obtained from ancient cysts. If sufficiently old cysts can be obtained in the future this system may also provide a way to evaluate the rate of nucleotide substitutions in selected genes over "real time".…”
Section: Discussionmentioning
confidence: 98%